2015
DOI: 10.1371/journal.pone.0137978
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17A and Neutrophils in a Murine Model of Bird-Related Hypersensitivity Pneumonitis

Abstract: Hypersensitivity pneumonitis (HP) is an immune mediated lung disease induced by the repeated inhalation of a wide variety of antigens. Bird-related hypersensitivity pneumonitis (BRHP) is one of the most common forms of HP in human and results from the inhalation of avian antigens. The findings of a recent clinical analysis suggest that in addition to Th1 factors, the levels of interleukin(IL)-17 and IL-17-associated transcripts are increased in the setting of HP, and that both IL-17A and neutrophils are crucia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…IFN-gamma resulted in an increase in CXCL9 mRNA expression by human alveolar epithelial type II or A549 cells [28]. In our previous study, we demonstrated that IL-17A and neutrophils were crucial for the development of pulmonary inflammation in murine models of acute HP [29]. Those inflammatory responses may contribute to CXCL9 production in HP patients.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-gamma resulted in an increase in CXCL9 mRNA expression by human alveolar epithelial type II or A549 cells [28]. In our previous study, we demonstrated that IL-17A and neutrophils were crucial for the development of pulmonary inflammation in murine models of acute HP [29]. Those inflammatory responses may contribute to CXCL9 production in HP patients.…”
Section: Discussionmentioning
confidence: 99%
“…Because populations of Siglec-F high Ly6G low SSC high eosinophils and alveolar macrophages were detected outside of the neutrophilgate, neutrophils expressing Siglec-F and CD11c were clearly distinguishable from other cells. Previous studies have shown that a subpopulation of activated neutrophils expressed Siglec-F and CD11c on the cell surface [21][22][23][24][25] . Siglec-F is known to be an inhibitory receptor that can be expressed in activated lung T cells as well as eosinophils 26 .…”
Section: Il-17a Was Required For the Generation And Maintenance Of Vamentioning
confidence: 98%
“…Previous studies suggest that neutrophils are required for the induction of multinucleated giant cells (MGCs) that can suppress the growth of Mycobacterium tuberculosis 27 . IL-17A-dependent granuloma formation is also known in murine tuberculosis 28 , cryptococcosis 29 , and hypersensitivity pneumonitis models 25 . Our previous study showed that MGC formation was correlated with protective response against pulmonary infection with highly virulent C. gattii 7 .…”
Section: Il-17a Was Required For the Generation And Maintenance Of Vamentioning
confidence: 99%
“…Human and animal studies suggest that reduced number or function of gd T cells (important in immune response attenuation) is associated with fibrosis in HP (38,68,69). IL-17A may be important, with reduced inflammation and less collagen formation when IL-17 is absent or neutralized (70)(71)(72). Neutrophils are implicated as the source of IL-17 (70), and are correlated with the extent of fibrosis in human fibrotic HP lungs (73).…”
Section: Management Of Fibrotic Hpmentioning
confidence: 99%